'For a Further Union': Conceptions of Unity in the Later W.B. Yeats and T.S. Eliot. Issue 1 (2nd January 2023) - Swanepoel, Charika
Abstract: This paper considers the shared preoccupation with unity in the later works of W.B. Yeats and T.S. Eliot with the aim of emphasizing the likeness in their thinking despite their vastly different theological stances. The unity strived for by both poets involves a dedicated resolution or transformation of contraries. Yeats scholars such as George Bornstein have termed Yeats's dedication to all things opposite his 'antinomial vision' and Eliot scholars such as Jewel Spears Brooker refer to Eliot's 'dialectical imagination'. This paper is aimed at further developing the established view of these comparable tendencies by pointing to a three-part pattern that emerges from Yeats and Eliot's later works. This pattern suggests a similar process behind their 'antinomial vision' and 'dialectical imagination' that entails: 1) a concern with opposites, 2) an ensuing inarticulacy, and 3) a capacity for incarnation. While this paper analyses Yeats and Eliot's individual contributions, it draws broad philosophical patterns between them and illustrates the similarities and parallels that incidentally emerge from the comparison.